Islam and the wisdoms of Asian religions - Cheng, Yamin (The Other Press, 2012)
This book is a result of the author's many years of personal reflections on the relationship between Islam and the wisdoms of China. These wisdoms are the wisdoms of Buddhism, Confucianism and Taoism, and together, they form the San Chiao, or 'Three Teachings' of the Chinese worldview. Through his Chinese legacy, the author tries to make connections with the Islamic worldview and finds they are inter-related in many ways. He discovers that Chinese wisdoms and practices are, to a large extent, Islamic. A Chinese who enters Islam, therefore, need not abandon his Chinese roots as he takes on the Islamic identity. He is already, in many ways, a Muslim even before entering Islam.